Mengarusutamakan Keberadaan Penyandang Disabilitas sebagai Subjek Pembangunan di Desa Sidoharjo - Dwi Saputra, Wahyu; Hanung, Gembong (Direktorat Pengabdian kepada Masyarakat, 2023)
People with disabilities are a socially, economically and politically vulnerable group. Even though their existence has been recognized in global norms such as the Sustainable Development Goals (SDGs), their role in development is still often perpetuated as objects rather than subjects of development. This study aims to understand how far the SDGs manifested in the